Validation of the Revised Impact of Miscarriage Scale for Swedish conditions and comparison between Swedish and American couples' experiences after miscarriage. (2nd November 2017) - Jansson, Caroline; Volgsten, Helena; Huffman, Carolyn; Skoog Svanberg, Agneta; Swanson, Kristen M.; Stavreus-Evers, Anneli
Abstract: Introduction: There is a lack of knowledge in women's and men's experience of miscarriage. The Revised Impact of Miscarriage Scale (RIMS) has been used in United States to measure the experiences after miscarriage. The first objective was to test the consistency of RIMS for Swedish conditions. The second purpose of this study was to compare Swedish and American couples' experience of miscarriage by use of the RIMS. Methods: Forward and back translation was used for translating RIMS into Swedish. This is a hospital-based comparative study including Swedish couples ( n  = 70) and American couples ( n  = 70). The couples were matched by the women's age, week of miscarriage and number of children. All participants answered socio-demographic, fertility and depression-scale questions in addition to RIMS. Results: Cronbach's alpha analysis was above 0.650, the mean value was 0.824. There was no significant difference between the Swedish and American participants on the factors 'Isolation/Guilt' and 'Devastating event', but the Swedish women and men scored significantly lower on the factor 'Loss of baby' than the American women and men. The men, Swedish and American combined, scored lower than the women in all factors but the correlation within the couples was similar for both Swedish and American couples. Conclusions: The high consistency between the countries suggests that the RIMS questionnaire is reliable for both women and men to be used in both countries and two of three factors were similar between the two countries.